Lucid dreaming increased during the COVID-19 pandemic: An online survey - Nunes, Priscilla Kelly da Silva Barros (2022)
The COVID-19 pandemic changed people's lives all over the world. While anxiety and stress decreased sleep quality for most people, an increase in total sleep time was also observed in certain cohorts. Dream recall frequency also increased, especially for nightmares. However, to date, there are no consistent reports focusing on pandemic-related changes in lucid dreaming, a state during which dreamers become conscious of being in a dream as it unfolds. Here we investigated lucid dreaming recall frequency and other sleep variables in 1,857 Brazilian subjects, using an online questionnaire. Firstly, we found that most participants (64.78%) maintained their lucid dream recall frequency during the pandemic, but a considerable fraction (22.62%) informed that lucid dreams became more frequent, whereas a smaller subset (12.60%) reported a decrease in these events during the pandemic. Secondly, the number of participants reporting lucid dreams at least once per week increased during the pandemic. Using a mixed logistic regression model, we confirmed that the pandemic significantly enhanced the recall frequency of lucid dreams (p = 0.002). Such increase in lucid dreaming during the pandemic was significantly associated with an enhancement in both dream and nightmare recall frequencies, as well as with sleep quality and symptoms of REM sleep behavior disorder. Pandemic-related increases in stress, anxiety, sleep fragmentation, and sleep extension, which enhance REM sleep awakening, may be associated with the increase in the occurrence of lucid dreams, dreams in general, and nightmares